The POWDER protocol as infrastructure to serving and compressing semantic data. (14th August 2012) - Konstantopoulos, S.; Archer, P.; Karampiperis, P.; Karkaletsis, V.
The POWDER protocol is a Semantic Web technology that takes advantage of natural groupings of URIs to annotate all the resources in a regular expression-delineated sub-space of the URI space. POWDER is a mechanism for accreditation, trustmarking and resource discovery, emphasising the publishing of attributed metadata by third parties and trusted authorities. Demonstrating its versatility, it has also been deployed in unforeseen use cases, such as repository compression. In this paper, we present the POWDER protocol, explain its position in the Semantic Web architecture, expose and discuss current implementations and use cases and future directions.